Green production information transparency and online purchase behavior: Evidence from green agricultural products in China - Fu, Shaoling; Liu, Xiaodan; Lamrabet, Abdesslam; Liu, Hua; Huang, Yatao (Frontiers in Environmental Science, 2022)
The “lemon effect,” which is the result of information asymmetry and barriers to trust, poses serious challenges to the sustainable development of green agricultural products. Therefore, it is vital to enhance consumer trust and maintain continuous purchasing behavior. Information transparency has been widely accepted as a marketing tool, and previous studies, especially those related to agricultural products, mainly focus on the visible information. To contribute to this literature, this study takes an invisible information perspective and empirically investigates how production information transparency concerning the means of production and technologies used affects consumer trust and online purchasing behavior. Based on signaling theory, a conceptual framework is developed and validated through a large-scale survey of consumers of green agricultural products in China. The results of structural equation modeling and bootstrapping analysis suggest that different forms of production information transparency have different effects on the dimensions of consumer trust (in competence and benevolence). While transparency of technology use is found to positively relate to trust in both competence and benevolence, transparency of production means only has a significant impact on trust in competence. An interrelation between trust in competence and trust in benevolence is also identified; they both have significant impacts on consumers’ online green purchase behavior. The results of this study contribute to signaling theory and the supply chain transparency literature, and offer significant insights to practitioners of the green agricultural sectors.